The characterization of microbial communities and associations in karst tiankeng - Jiang, Cong; Liu, Yuanmeng; Li, Hui; Zhu, Sufeng; Sun, Xiang; Wu, Kexing; Shui, Wei (Frontiers in Microbiology, 2022)
The karst tiankeng is a special and grand negative terrain on the surface, that maintains a unique ecosystem. However, knowledge about bacterial and fungal communities in karst tiankengs is still limited. Therefore, soil samples from five karst tiankengs were collected and subjected to high-throughput sequencing of 16S rRNA and ITS genes, and multivariate statistical analysis. The results showed abundant and diversified bacterial and fungal communities in karst tiankeng. The bacterial communities were dominated by Proteobacteria and Acidobacteria, and the fungal communities were dominated by Ascomycota and Basidiomycota. Statistical analysis revealed significant differences in bacterial and fungal communities among the five karst tiankengs, which may indicate that the distribution of bacterial and fungal communities was driven by separate karst tiankengs. The co-occurrence network structure was characterized by highly modularized assembly patterns and more positive interactions. The keystone taxa were mainly involved in nutrient cycling and energy metabolism. The null model analysis results showed that the stochastic process, especially dispersal limitation, tended to be more important in controlling the development of bacterial and fungal communities in karst tiankeng. The bacterial community structure was significantly associated with soil properties (SWC, TN, AN, and BD), while the fungal community structure was significantly associated with soil properties (SWC and TP) and plant diversity. These results can expand our knowledge of the karst tiankeng microbiome.